Does Transitioning Towards Renewable Energy Accelerate Economic Growth? An Analysis of Sectoral Growth for a Dynamic Panel of Countries - Doytch, Nadia (Archīum Ateneo, 2021)
This study examines the impact of non-renewable and renewable energy consumption on economic growth, differentiating between manufacturing and services growth. We derive our empirical model from an endogenous growth framework with expanding variety of intermediate capital goods embedding non-renewable and renewable energy inputs. Controlling for well-established growth determinants, we estimate the effects of non-renewable and renewable energy consumption, differentiated by type of use — industrial, residential, and total final energy consumption — on manufacturing and services growth. We find that renewable energy enhances growth in high-growth sectors, i.e. the services sector in high-income economies and the manufacturing sector in middle-income economies. In the case of high-income countries, renewable energy is a complement to non-renewables, whereas in the case of middle-income countries the two are substitutes. The growth effects are primarily due to industrial energy consumption. T Based on our findings, we propose that an effective renewable energy incentives policy for middle-income countries should be directed at manufacturing enterprises, and in high-income countries these incentives should be directed at the services sector.